2005
DOI: 10.1007/s00262-005-0061-2
|View full text |Cite
|
Sign up to set email alerts
|

The biological effects of syngeneic and allogeneic cytokine-expressing prophylactic whole cell vaccines and the influence of irradiation in a murine melanoma model

Abstract: Allogeneic whole tumour cell vaccines are inherently practical compared with autologous vaccines. Cell lines are derived from allogeneic tumour, grown in bulk and then administered as a vaccine to the patient, following irradiation, which not only prevents any replication but also enhances antigen presentation. Protection is believed to occur through the presentation of antigens shared between the syngeneic and allogeneic tumours. Although cytokine-transfected tumour whole cell vaccines have been used clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…5) indicate that the surface marker density may reduce from 10% for most markers up to 30% for CD9 in the OnyCap23 cell line. The retention of antigen load of the correct conformation is generally accepted as being a good surrogate of vaccine activity for more established vaccines and evidence suggests that in vivo cells are lysed and processed by the immune system within 9 days post‐injection (Labarthe et al, 2006). However, for novel, cell‐based therapeutic vaccines antigen density or confirmation alone may not be a sufficient surrogate, as the intended biological effect in vivo is often not clear, and cell membrane integrity may also be important (European Medicines Agency, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…5) indicate that the surface marker density may reduce from 10% for most markers up to 30% for CD9 in the OnyCap23 cell line. The retention of antigen load of the correct conformation is generally accepted as being a good surrogate of vaccine activity for more established vaccines and evidence suggests that in vivo cells are lysed and processed by the immune system within 9 days post‐injection (Labarthe et al, 2006). However, for novel, cell‐based therapeutic vaccines antigen density or confirmation alone may not be a sufficient surrogate, as the intended biological effect in vivo is often not clear, and cell membrane integrity may also be important (European Medicines Agency, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…This approach holds promise because many tumors of the same histiotype may share common antigens, so that vaccination against one tumor may elicit cross-reactive immune responses against other tumors of the same type. 34,40,41 An allogeneic tumor lysate vaccine for melanoma has been evaluated in a number of clinical trials in humans and has shown clinical benefit in an adjuvant setting. 42,43 Vaccines prepared with tumor cell lysates are particularly promising because of the ease of preparation, storage, and shipping of the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animal models indicate that vaccination with an allogeneic tumor of the same type (i.e., melanoma treated with a melanoma cell line) can induce rejection of a tumor while treatment with cell lines of a different cancer background does not [20,21] and, moreover, they can subsequently induce strong responses to autologous cell lines. However, not all allogeneic melanoma cell lines were protective in a melanoma model indicating a level of heterogeneity within cancer lines of the same type [20].…”
Section: Vaccines Using Unmodified Autologous or Allogeneic Cellsmentioning
confidence: 99%